McGraw-Hill Concise Encyclopedia of Chemistry (American : McGraw -Hill, 2004)
Choice, Feb. 2005
meet[s]...goal ("providing the reader with essential knowledge in chemistry without extensive detail")...[from]high school through lower undergraduate...low-cost alternative
Review
Excerpts from review by K. L. Carriveau Jr., Baylor University
Entries in this work were extracted and condensed from McGraw-Hill Encyclopedia of Science & Technology (9th ed., 20v., CH, Sep'02)... Although this version seems to meet its goal ("providing the reader with essential knowledge in chemistry without extensive detail")...the biographical section included as an appendix is useful and addresses a common need of students from high school through lower undergraduate levels...Although many of the 700 entries are dated, they are still valid and the concise edition will be valuable to special collections looking for a low-cost alternative to the full 20-volume set.... (Choice )
Keywords: Chemistry- Encyclopedia